2011
DOI: 10.1143/apex.4.053101
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of FeSe0.5Te0.5Thin Films on CaF2Substrates with High Critical Current Density

Abstract: In-situ epitaxial growth of FeSe 0.5 Te 0.5 thin films is demonstrated on a nonoxide substrate CaF 2 .Structural analysis reveals that compressive stress is moderately added to 36-nm-thick FeSe 0.5 Te 0.5 , which pushes up the critical temperature to above 15 K, showing higher values than that of bulk crystals. The critical current density at T = 4.5 K reaches 5.9 × 10 4 Acm −2 at µ 0 H = 10 T, and 4.2 × 10 4 Acm −2 at µ 0 H = 14 T. These results indicate that fluoride substrates have high potential for the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 27 publications
10
107
2
Order By: Relevance
“…However, because superconducting FeTe films can have both longer and shorter a-axis length [124], the mechanism seems not simple like the strain scenario by Han et al [122], whereas the superconducting properties of FeTe may be largely affected by the lattice strain, suggested by thermal expansion measurements [126]. Physical properties of the superconducting FeTe are similar to those of FeSe 1−x Te x : (1) strain largely affects the T c values [126]; (2) importance of both n-and p-type carriers for the superconductivity, suggested by the Hall effect [40,127,128]; (3) huge B c2 (> 30 T) [122,123,129]. These may suggest that the mechanism of the superconductivity is the same for both FeTe and FeSe 1−x Te x .…”
Section: -Systemmentioning
confidence: 92%
See 4 more Smart Citations
“…However, because superconducting FeTe films can have both longer and shorter a-axis length [124], the mechanism seems not simple like the strain scenario by Han et al [122], whereas the superconducting properties of FeTe may be largely affected by the lattice strain, suggested by thermal expansion measurements [126]. Physical properties of the superconducting FeTe are similar to those of FeSe 1−x Te x : (1) strain largely affects the T c values [126]; (2) importance of both n-and p-type carriers for the superconductivity, suggested by the Hall effect [40,127,128]; (3) huge B c2 (> 30 T) [122,123,129]. These may suggest that the mechanism of the superconductivity is the same for both FeTe and FeSe 1−x Te x .…”
Section: -Systemmentioning
confidence: 92%
“…On the other hand, Naito et al reported that the SmFeAsO (Sm1111) film on CaF 2 substrate with a cap layer of SmF 3 fabricated by MBE showed a superconducting transition at ∼56 K which was slightly higher than T c of SmFeAs(O,F) bulk samples [38,39]. Although CaF 2 was firstly used by Tsukada et al as a substrate material in the film growth of FeSe 1−x Te x [40], which will be discussed later, the enhancement of T c also in Sm1111 film on CaF 2 [38] shows that CaF 2 is efficient for the thin film growth of other iron-based superconductors. In these reports, the extra cap layer is necessary to obtain a superconducting 1111 film, which prevents an application of 1111 film for a sandwich-type junction [36,38].…”
Section: -Systemmentioning
confidence: 99%
See 3 more Smart Citations